Killing Times : The Temporal Technology of the Death Penalty - Wills, David, 1953- (Book collections on Project MUSE., 2019)
Grounded in a deep ethical and political commitment to death penalty abolition, Wills's engaging and powerfully argued book pushes beyond the confines of legal argument to show how the technology of capital punishment defines and appropriates the instant of death and reconfigures the whole of human mortality.